Fibronectin in the Tumor Microenvironment Activates a TLR4-dependent Inflammatory Response in Lung Cancer Cells - Cho, Christina (J Cancer, 2020)
The microenvironment of solid tumors plays an essential role in tumor progression. In lung cancer, the stromal cells produce a fibronectin rich extracellular matrix which is known to contribute to both tumor metastasis and drug resistance. Due to its conformational lability, fibronectin is considerably remodeled by the contractile forces of the fibrotic microenvironment within the tumor stroma. As a result, the secondary structure of fibronectin's Type III domains is disrupted and the molecule becomes highly stretched. The contribution/impact of these strained forms of fibronectin on tumor growth and metastasis is not known. In the current study we show that the partially unfolded first Type III domain of fibronectin, III-1c, activates a toll-receptor/NF-κB pathway leading to an increase in the expression of IL-8. Using a 3-D model of tumor-associated extracellular matrix, we demonstrate that lung cancer cells seeded onto this matrix activate a TLR4/NF-κB signaling pathway leading to a robust increase in the release of IL-8. Cytokine release by these cells is completely dependent on the presence of fibronectin in the extracellular matrix. These findings suggest that paracrine signaling between the tumor and the stromal myofibroblasts causes a remodeling of the matrix fibronectin into a strained conformation which supports the activation of a TLR4/NF-κB signaling pathway resulting in the upregulation of fibro-inflammatory cytokines.